Consideration on Local Heat Transfer Measurement of Plate Heat Exchanger with the Aid of Simulation - Thiha Tun; Keishi Kariya; Akio Miyara (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2020)
Abstract In this study, the local heat transfer coefficient of boiling and condensation were obtained by an experimental set up using vertical stainless-steel type brazed plate heat exchanger. A series of 8 vertical brazed plates are used as the major components of the test section of experimental set up and are fabricated into layers so that flow channels are formed between the plates through which water and refrigerants are flowing through. The experiments are carried out at the mass flux of 10, 20 and 50 kg/(m2s). In order to measure the local heat transfer coefficient, flat stainless-steel plates of 10 mm in thickness are installed attached to the vertical plates onto which the thermocouples are positioned to measure the temperature distributions at the surface of the plates. By performing the experiment, the direction of the heat flux across the plate tends to deviate downward especially at the lower part of the plate due to the non-uniform temperature distributions across the plate. The results are analyzed and validated at the mass flux of 10 kg/(m2s) by the aid of the simulation tool by using ANSYS FLUENT 19.1 to estimate the local heat transfer coefficient and the heat flux across the plate. The analysis result shows that the simulation model can assist to track the deviation of the direction of the heat flow from the horizontal direction across the plate and the experimental results of the local heat transfer coefficient have similar trends with that of the simulation results.